The values of character education in a novel Nun: Pada Sebuah Cermin by Afifah Afra - Yusuf Muflikh Raharjo; Sarwiji Suwandi; Kundharu Saddhono (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
Novel be one of the teaching materials able to provide much in value education for his stories novel very close to human beings. There is also we can find big number of research that appears to dissect the content of educational values in a novel with the aim of making it easier for teachers to teach the values of education to the students. This study aims to describe about content of character education values in a novel Nun: Pada Sebuah Cermin by Afifah Afra.This study focused to discover about the content of characters, such as (1) religious, (2) honest, (3) discipline, (4) hard work, (5) self-reliance, (6) social care, and (7) responsibility that is in the novel. The research is descriptive method of qualitative data sources used the sociology of literature in the form of a novel. The result of this research the findings of characters education can be applied into learning at school, especially senior high school Basic Competence (KD) 3.1 and 4.1 through the use of novel be a source of learning.